What Direction for Oil Prices? - Claudia Kemfert; Manfred Horn (Weekly Report, 2005)
The price of crude oil goes up and up -most recently driven by hurricane Katrina, which had a catastrophic effect on the US oil industry, and was followed by hurricane Rita. In September 2005 the price of Brent crude reached a new record at US 66 per barrel. The agreement by member states of the International Energy Agency (IEA) to release crude oil and petroleum products from their strategic reserves has brought prices down again slightly, but it is very questionable whether this will calm the upward drive for long. Crude oil prices have been rising continuously since 2003, largely as a result of increased demand, particularly from China. The high level of capacity utilization in oil extraction creates risks that are reflected in rising prices on the forward markets. The rise in oil prices since 2003 is around US 30 per barrel, and this is probably mainly due to short-term effects and resultant speculative buying. In view of the high stocks of oil the current prices do seem excessive. Sooner or later they will normalize on a lower level, but in the long term higher prices for oil than the average of recent decades must be expected. Model simulations up to the year 2025 show that in a scenario of adequate resources real oil prices (price base 2000) of between US 30 and US 40 per barrel are to be expected. In a scenario of more limited resources, however, prices could rise to just under US 80 per barrel in real terms, which is up to US 160 nominally.
Keywords: 330